Bitcoin and the Japanese retail investor - Grinenko, Maksym (2019)
The objective of this research is to examine the Bitcoin rally of 2017 as it occurred in Japan and establish a greater context for why it was the Japanese retail investors that propelled the nation to being the largest trader of the cryptocurrency at the end of the year. This dissertation begins with the examination of the technical and economical properties of Bitcoin by classifying it as fulfilling two roles: that of a means of payment and that of an investment commodity. Following that is a description of Bitcoin’s roots and the history of its non-speculative usage. These chapters serve as a base for examining the cryptocurrency’s role in Japan. The third chapter examines the Japanese retail investor and the Japanese retail investment landscape with a focus on the question of the low rates of risk-asset participation in face of a favorable investment environment. Historical context is drawn upon to argue that the present situation, wherein most financial assets are kept as cash, is rather the result of the historical path dependence than the present-day conditions in which Japanese retail investors operate. The final chapter addresses the question of high-risk activities in the form of gambling and margin trading by a group of predominantly middle-aged men and connects this propensity to engage in zero-sum games with Bitcoin’s success in Japan. The author argues that the solitary practice of high-risk financial activities enabled by trusted institutions is separate from the general savings tradition that suffered shocks following the low interest-rate regime and that it was the high-risk gambles that became the primary cause for the popularity of Bitcoin. The dissertation concludes with the argument that the success of Bitcoin in 2017 had been in no small part achieved precisely by inverting the hard-line libertarian values of its creators and making it a centrally-held commodity offered by a banking-like institution with a strong public presence.